Deconstructing the Portrayal of Adults’ Superiority towards Children in Frances Hodgson Burnett’s "A Little Princess" (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
This study discusses how the portrayal of adults’ superiority towards children in the novel A Little Princess by Frances Hodgson Burnett is deconstructed by the work itself. The adults’ superiority is portrayed in the novel, in which the adults are depicted as more superior figure than children. However, the perfect descriptions of the children as portrayed by Sara in the novel show that the hierarchy in child-adult relationship is able to be reversed. This study uses descriptive qualitative method supported by Structuralism’s binary opposition and Derrida’s Deconstruction reading strategy. The aim of this study is to destabilize the novel, A Little Princess, by applying Deconstruction reading strategy. This study shows that the novel deconstructs its portrayal of adults’ superiority towards children. So, by destabilizing the binary opposition in the novel, that is an adult opposes a child, the child-adult hierarchy is reversed. Keywords: adults, children, deconstruction, superiority